Analisis dan Implementasi Sistem Informasi Persewaan Alat dengan metode Rapid Application Development - Rahman Abdillah; Rudi Hermawan; Adhityo Kuncoro; Andreas Adi Trinoto; Fikri Hizryan; Heri Arifin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Software design using the RAD methodology has been widely used among practitioners and academics. One of the advantages of using RAD is the rapid development of software systems. In this paper, the authors employ the RAD method as a software development approach for a service business in the rental equipment information system. The purpose of this paper is to contribute scholarly recommendations regarding the use of RAD methodology in the design of rental equipment information systems. The research methods utilized in this paper are literature review and software system implementation. In relation to the implementation stage, the author utilizes the Java programming language and MySQL as the database. The results obtained from this paper include the faster development of software quality and the recommendation of screen design prototypes that can be used by software developers involved in similar rental service businesses.